ANALISIS TINGKAT KESESUAIAN ASESMEN PEMBELAJARAN DENGAN CAPAIAN PEMBELAJARAN PADA KURIKULUM MERDEKA DI SEKOLAH DASAR - Attalikhtia, Wiwit; Susilo, Hari; Windi Setiawan, Ahmad; Sutarni, Sri; Ghufron, Anik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of the Independent Curriculum requires a paradigm shift in learning assessments to align with Learning Outcomes (CP) and support student-centered learning. However, in practice, there are still discrepancies between teacher-designed assessments and the requirements of the Independent Curriculum, particularly in the application of diagnostic assessments and learning differentiation. This study aims to analyze the level of alignment of teacher-implemented learning assessments with the Learning Outcomes in the Independent Curriculum at SDN Margapadang 1. The study used a quantitative approach with a descriptive design. The research subjects consisted of 11 teachers from grades I to VI. Data were collected through structured questionnaires and document analysis of teacher-designed assessment tools. Data analysis was conducted using descriptive statistics by calculating the percentage of balance based on indicators developed from the Independent Curriculum regulations. The results showed that the level of alignment of learning assessments with Learning Outcomes was in the moderate category, at 68.4%. Formative assessments had a higher level of alignment (74.2%) than summative assessments (62.6%). The aspect with the highest level of conformity was the variation in assessment techniques (78.3%), while the lowest was the implementation of cognitive diagnostic assessments (54.1%). Research findings indicate that teachers have begun implementing the assessment principles of the Independent Curriculum, but still need to strengthen their competencies in designing diagnostic assessments, developing instruments aligned with Learning Outcomes, and implementing adaptive assessments according to student characteristics and needs.